2012
DOI: 10.1108/17511061211280347
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and international strategies in the Queensland wine industry

Abstract: PurposeOver the past decade, the Queensland wine industry has experienced a greater percentage growth than the Australian national average. The aim of the research undertaken for this article is to identify specific national and international strategies that have allowed the industry to achieve this level of growth.Design/methodology/approachThe study involved a quantitative survey of all Queensland wineries at the time (n=101), using a five‐point Likert‐scaled questionnaire with questions developed from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Collaboration among stakeholders has often been found to be a key success factor in wine tourism, as several authors have already observed. This merits further research, as has previously been observed by Bamberry and Wickramasekara (2012).…”
supporting
confidence: 69%
“…Collaboration among stakeholders has often been found to be a key success factor in wine tourism, as several authors have already observed. This merits further research, as has previously been observed by Bamberry and Wickramasekara (2012).…”
supporting
confidence: 69%
“…Furthermore, some studies have studied specific regions of certain wineproducing countries; for example, Telfer (2001) explored the strategic alliances of vineyards and wineries in Canada's Niagara region, finding that cooperation with vertical (e.g., supply chain partners) and horizontal (e.g., competitors) partners can improve firms' wine tourism offerings. The wine industry provides scholars with an empirical context to study certain phenomena, with such a setting allowing researchers to build and/or test broader management theories (Bamberry and Wickramasekara, 2012). Furthermore, Crick (2018) utilised the "New Zealand Winegrowers' database", and identified a sub-set of this population to interview, observe, and indeed contact due to having access to such archival information.…”
Section: Wine Business Research and Empirical Contextsmentioning
confidence: 99%
“…competitors) partners can improve firms' wine tourism offerings. The wine industry provides scholars with an empirical context to study certain phenomena, with such a setting allowing researchers to build and/or test broader management theories (Bamberry and Wickramasekara, 2012).…”
Section: Wine Business Research and Empirical Contextsmentioning
confidence: 99%
See 1 more Smart Citation